Darurat Kualitas Pendidikan: Peran Krusial Kepala Sekolah Dalam Mencari Solusi Melalui Manajemen Mutu - Ahmad Hadiq Syifa Al Fawaz; Siti Aimah (Journal on Education, 2025)
The purpose of this study is to analyze the strategic role of school principals in implementing quality management to overcome the emergency challenges of education quality in the modern era. This research departs from the argument that school principals are key actors who have direct authority and responsibility in ensuring the quality of education services in schools. In the context of an education quality emergency, where challenges such as low learning outcomes, limited resources and rapid technological developments affect the education ecosystem, school principals are expected to develop a comprehensive and sustainable quality management strategy. This research method uses a qualitative approach with a case study design to understand the role of school principals in implementing quality management strategies amid the education quality crisis. The research involves in-depth interviews, direct observation and documentation to collect data from principals, teachers and administrative staff. Thematic analysis will be used to identify key themes related to quality management implementation. The results of this study show that principals play a crucial role in improving education quality through transformational leadership, implementing a data-based supervision system and strengthening teachers' competencies. Inspirational and collaborative leadership creates a sustainable culture of quality while data-based supervision enables more informed and measurable decisions. Teacher professional development through regular training is also important to improve teaching skills and create more meaningful learning experiences for students.